2020
DOI: 10.48550/arxiv.2004.03318
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Classification of rank two weak Fano bundles on del Pezzo threefolds of degree four

Abstract: We classify rank two vector bundles on a given del Pezzo threefold of degree four whose projectivizations are weak Fano into seven cases. We also give an example for each of these seven cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
13
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Classifications on del Pezzo 3-folds of degree ≤ 2. By Theorem 1.1 and our previous studies [13,8], we obtain the classification result on del Pezzo 3-folds X of degree 3 ≤ deg X ≤ 5. To complete our classification, we show there exist no nontrivial weak Fano bundles when the case deg X ≤ 2, which is namely the following theorem.…”
supporting
confidence: 52%
See 4 more Smart Citations
“…Classifications on del Pezzo 3-folds of degree ≤ 2. By Theorem 1.1 and our previous studies [13,8], we obtain the classification result on del Pezzo 3-folds X of degree 3 ≤ deg X ≤ 5. To complete our classification, we show there exist no nontrivial weak Fano bundles when the case deg X ≤ 2, which is namely the following theorem.…”
supporting
confidence: 52%
“…Briefly speaking, we showed that every indecomposable weak Fano bundle is either a Fano bundle or a vector bundle E with c 1 (E) = 0 such that E(1) is globally generated. By the same approach as in [8], we will see that this phenomenon still holds when deg X = 5 (see Section 5.3).…”
mentioning
confidence: 74%
See 3 more Smart Citations